Rambak Product Differentiation Training and Mentoring to Improve Branding in Kandangsapi Subdistrict - Fitriyah Ulfah; Yulina Lailatul Maslukhah; Dini Pratiwi; Karina Nur Aini; Shofiyatul Laili (Bakti Cendana, 2026)
To increase the potential of small businesses in Kandapi Village, Panggungrejo District, Pasuruan City. In community service activities, students strive to improve the quality and marketing of the product "Rambak Ibu Ulfah", this local business is 20 years old. This product differentiation activity includes: creating new packaging designs, innovating flavor variants, and implementing online marketing through social media platforms. The results of this activity include online marketing training, creating promotional content, and establishing an outlet at the Business Center of SMKN 1 Pasuruan. The evaluation showed a positive response to product innovation. From the results of the product differentiation activities that have been carried out, the profit obtained reached IDR 56,000 from the sale of 30 small-packaged rambak and 15 large-packaged rambak. In addition, this activity was able to create branding for rambak products by providing elements of the Pasuruan City logo to attract consumers from all walks of life outside the city